Self-regulation of journalism in Spain - A. N. Rylova (Ибероамериканские тетради, 2015)
Self-regulation of journalism resides in voluntary measures taken by the professional community of journalists to guarantee the observation of certain rules and principles in the process of providing information to public, maintain independence and credibility of media. The institution of self-regulation of Spanish journalism emerged later than in other Western countries due to the history of interaction between the State and media: for a long time Spanish media were under State control and freedom of expression was constantly defied. That is why first attempts to establish bodies for self-regulation of journalism in the post-Franco Spain evoked fears of a return to censorship. However, the time lag concerning media self- regulation allowed Spain to use other countries’ experience. Nowadays, the degree of self-regulation of journalism in Spain is similar to that of the Western countries. The institution of self-regulation operates successfully and facilitates Spanish media authority.